2000
DOI: 10.1097/00007632-200012010-00006
|View full text |Cite
|
Sign up to set email alerts
|

Does Long-Term Compressive Loading on the Intervertebral Disc Cause Degeneration?

Abstract: Compression applied to the lumbar intervertebral discs of dogs for up to a year does not produce degeneration in any visible form. It does produce microscopic changes and numerical changes, however, in the amounts of proteoglycan and collagen in the nucleus, inner anulus, and outer anulus. The present results add no credence to the commonly held belief that high compressive forces play a causative role in disc degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
68
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(72 citation statements)
references
References 25 publications
4
68
0
Order By: Relevance
“…It is possible that the process of restructuring is not fully completed after 28 days of compression treatment. This is supported by reports from Hutton et al [8] showing first visible changes after compression treatment on a gene expression level hours to days after initiating load. In contrast, on a biochemical basis visible changes were found after months.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…It is possible that the process of restructuring is not fully completed after 28 days of compression treatment. This is supported by reports from Hutton et al [8] showing first visible changes after compression treatment on a gene expression level hours to days after initiating load. In contrast, on a biochemical basis visible changes were found after months.…”
Section: Discussionsupporting
confidence: 82%
“…Disc degeneration in animal models is still a matter of debate [1,[8][9][10][11][12][13]. Most studies with mechanically induced disc degeneration demonstrated a correlation between compression force and disc degeneration [1, 9, Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28,29 Animal models can clarify pathomechanisms and aid in development of therapeutic strategies. While most animal models require mechanical or chemical induction, 4,[29][30][31][32][33][34][35][36][37][38] the macaque has naturally degenerating intervertebral discs (Fig. 1).…”
mentioning
confidence: 99%
“…In these studies, static compressive loads were applied to the discs via pins inserted into the adjacent vertebrae. The compressive load was created by coiled metal springs [14,16], cantilever metal springs [26], or Fig. 4 Typical load-displacement curves of the discs in sham and compression groups after the 2-week experimental period.…”
Section: Rationale Of the Experimentsmentioning
confidence: 99%